Money Loundring Dalam Tindak Pidana Khusus - Luthfi Fahrezi Mahfuzh; Ali Akbar Sinambela; Jay Saalidin Ritonga; Ari Anugrah; Syarifuddin Syarifuddin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Money laundering is a complex, organized, and transnational economic and financial crime that poses a serious threat to the stability of the financial system and the national economy. This study aims to analyze the categorization of money laundering as a specific criminal offense and the substance of its regulation in Law Number 8 of 2010. The research method used is normative legal research with a legislative and conceptual approach through a literature study. The results of the study show that the regulation of money laundering outside the Criminal Code is an application of the lex specialis derogat legi generali principle, which provides a legal basis for the use of special mechanisms, such as the expansion of legal subjects to include corporations, the tracing and confiscation of assets derived from crime, and limited reverse burden of proof. This regulation is considered effective in supporting law enforcement and cutting off the flow of funds derived from criminal acts.